NEUROPSYCHOLOGICAL STUDY OF HOW SHOPPERS HANDLE DUBIOUS TRANSACTIONS AND MAKE ONLINE PAYMENTS - Krishnan Rajagopal, Navaneetha; Ramkumar, Gowtham; Yousoof, Muhammed; Priyadarshi Tripathi, Dr. Abhinav; S. Kakade, Dr. Kiran; Sharma, Dr. Nitin (The journal of contemporary issues in business and government, 2022)
Future online payments are critical for the promotion of future online transactions (e-payments). However, little research has been done on the variations in different systems between secure and risky e-payments, as well as customer reactions. E-commerce encompasses a broad variety of online services and goods, as well as electronic networks for the transfer of funds and data. Various applications are used in the e-commerce industry. The trust in Ecommerce relies primarily on the online payment system that allows the customer to pay for an online trader. This trial focuses on Neuroscience (fMRI) and I identify secure e-payment and risky neural effects. The underlying brain mechanisms are revealed in the face of two broad specific systems: PayPal and debit cards are accepted. Thirty people took part in an experiment that simulated low-cost online shopping. Risky e-payments cause cortical areas associated with unwanted emotional processing, but highly secure e-payments do not, according to the report. PayPal is about more than just dependability, incentive, and effectiveness. In addition, the study revealed payments, by contrast, generate brain activation in relation to negative and risky events with the debit card. It is interesting that the right brain response has been used more positively (responsible for value encoding). These findings provide a precious overview of the unconscious origins of consumers' choice of payment systems.